Reinforced Granular Hydrogels Scaffolds with Tunable Physicochemical Properties for Advanced Skin Tissue Engineering - Jing Zhang; Yijia Wang; Yue Liu; Guanfu Wu; Guilong Lu; Yue Li; Yu Shen; Caifeng Wang; Mehdi Khanmohammadi; Wojciech Święszkowski; Jing Wang; Ziyi Yu (Advanced Science)
Abstract Engineering bioscaffolds with tailored architectures and optimized physicochemical properties remains a crucial yet challenging goal in tissue engineering and regenerative medicine. In this study, the design of reinforced concrete‐inspired annealed granular hydrogel (GH) scaffolds that meet the essential yet often conflicting requirements for bioscaffolds: providing adequate mechanical strength while facilitating cell infiltration, nutrient exchange, and the formation of complex cellular networks. GH building blocks are synthesized using a binary macromonomer system of hyperbranched polyethylene glycol and thiolated gelatin within microfluidic droplets, benefiting from the molecular interface assembly and templating effects of the microdroplets, which possess highly reactive vinyl functional groups, thereby endowing the annealed GH scaffolds with highly customizable properties. The versatility of this platform is demonstrated by the creation of full‐thickness engineered skin tissues that support keratinocyte attachment and differentiation; the formation of a mature epidermis, complete with a developed stratum corneum, and the expression of key markers, such as keratin 10 and keratin 14, while minimizing contraction over long‐term culturing, a common limitation of traditional collagen‐based scaffolds. Owing to their biocompatibility, tunable mechanical properties, ease of surface functionalization, and compatibility with bioprinting, these scaffolds have significant potential for applications in tissue engineering, drug delivery, and bioprinting.